1998
DOI: 10.1016/s0378-5955(98)00142-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mannitol upon cochlear dysfunction induced by transient local anoxia

Abstract: Transient local anoxia of the cochlea was induced by pressing the labyrinthine artery, and compound action potential (CAP) or endocochlear potential (EP) was measured before and after transient local anoxia ranging from 5 to 60 min using 106 albino guinea pigs. The complete interruption of the cochlear blood flow by this procedure and its full restoration after releasing the pressure on the artery was confirmed by a laser-Doppler flowmeter. The anoxia of less than 10 min induced no post-anoxic cochlear dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 33 publications
3
33
1
Order By: Relevance
“…Morphologic changes within the cochlea detected during transient (<15 min) hypoxia or anoxia, includes swelling of the OHC and afferent nerve endings beneath the IHC (40,41). These ultrastructural alterations, coupled with electrophysiological measurements (42)(43)(44), consistently appear in the basal turn region and demonstrate the sensitivity of the cochlea to ischemia. In the current study, the recovery of DPOAE after IAA occlusion was directly related to frequency.…”
Section: Discussionmentioning
confidence: 98%
“…Morphologic changes within the cochlea detected during transient (<15 min) hypoxia or anoxia, includes swelling of the OHC and afferent nerve endings beneath the IHC (40,41). These ultrastructural alterations, coupled with electrophysiological measurements (42)(43)(44), consistently appear in the basal turn region and demonstrate the sensitivity of the cochlea to ischemia. In the current study, the recovery of DPOAE after IAA occlusion was directly related to frequency.…”
Section: Discussionmentioning
confidence: 98%
“…In an initial period of strial dysfunction, there is a possibility of recovery, but prolonged loss of EP (when there is severe hypoxia) may result in permanent sensory damage. This notion is based on studies that have reported cochlear dysfunction with partial recovery after short periods of severe hypoxia or anoxia (e.g., Perlman et al 1959;Schulte and Schmiedt, 1992;Tabuchi et al 1998) but with permanent sensorineural hearing loss after very long periods of oxygen deprivation (e.g., Billett et al 1989;Tabuchi et al 1998;Sawada et al 2001). If the initial target of a viral infection is the stria vascularis, then with early detection and diagnosis, perhaps, some treatment for recovery is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The level of natural glutathione within the OHCs at the basal cochlea was found to be significantly lower than that at the apical turn, confirming a key role of the glutathionedependent antioxidant system in protection against various factors damaging cochlear function (Sha et al, 2001). Radical scavengers, iron chelators and nitric oxide synthase inhibitors attenuated the damaging effects of ROS following ischemia/reperfusion episodes by enhancing efficacy of the antioxidant system within the cochlea (Morawski et al, 2003c;Tabuchi et al, 1998Tabuchi et al, , 2001a.…”
Section: Discussionmentioning
confidence: 84%
“…Analysis of EP recovery pattern accompanying reperfusion of the cochlea showed that there is no simple relation between EP and other measured parameters of hearing status. Tabuchi et al (1998Tabuchi et al ( , 2002 showed that when EP reached a steady level 20 min following the onset of reperfusion, cochlear microphonics remained significantly reduced while a slow CAP improvement was observed. DPOAE recovery patterns recorded following reperfusion showed much slower recovery than EP (Rebillard and Lavigne-Rebillard, 1992;Mom et al, 1997).…”
Section: Discussionmentioning
confidence: 99%